Pratyā kh̨̄ong kānb̨̄orihān phāk rat - W̨̄oradēt Čhantharas̨̄on (ʻĒkkasān wichākān pī h̄æng kānsongs̄œm kānb̨̄orikān prachāchon kh̨̄ong rat, 1996)
On public administration philosophy; study with reference to Thailand.